Colonization of the Americas, 'Little Ice Age' climate, and bomb-produced carbon: Their role in defining the Anthropocene. (August 2015) - ,; Zalasiewicz, Jan; Waters, Colin N; Barnosky, Anthony D; Cearreta, Alejandro; Edgeworth, Matt; Ellis, Erle C; Gałuszka, Agnieszka; Gibbard, Philip L; Grinevald, Jacques; Hajdas, Irka; Ivar do Sul, Juliana; et al.
A recently published analysis by Lewis and Maslin (Lewis SL and Maslin MA (2015) Defining the Anthropocene. Nature 519: 171–180) has identified two new potential horizons for the Holocene−Anthropocene boundary: 1610 (associated with European colonization of the Americas), or 1964 (the peak of the excess radiocarbon signal arising from atom bomb tests). We discuss both of these novel suggestions, and consider that there is insufficient stratigraphic basis for the former, whereas placing the latter at the peak of the signal rather than at its inception does not follow normal stratigraphical practice. Wherever the boundary is eventually placed, it should be optimized to reflect stratigraphical evidence with the least possible ambiguity.